2003
DOI: 10.1111/j.0303-6987.2004.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumefactive lipedema with pseudoxanthoma elasticum‐like microscopic changes

Abstract: This tumefactive presentation of lipedema has not been previously described. Regarding the elastic-tissue abnormalities, the patient could have either a subclinical form of PXE, perhaps predisposing to lipedema, or secondary elastic-tissue changes resulting from the massive edema. If the latter is the case, then this could represent an unusual manifestation of localized acquired cutaneous PXE (calcific elastosis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…The elasticity of the skin and fascia is decreased in lipedema [132] which in Stage III may progress to abnormally clumped elastic fibers or pseudoxanthoma [133] . The skin loses its role as an abutment for the skeletal muscle venous pump and the increased compliance of the SAT results in an increase in capillary compliance [116,124] .…”
Section: Physiology Of Lipedema Satmentioning
confidence: 99%
“…The elasticity of the skin and fascia is decreased in lipedema [132] which in Stage III may progress to abnormally clumped elastic fibers or pseudoxanthoma [133] . The skin loses its role as an abutment for the skeletal muscle venous pump and the increased compliance of the SAT results in an increase in capillary compliance [116,124] .…”
Section: Physiology Of Lipedema Satmentioning
confidence: 99%
“…Our patient also had horizontal and oblique mental creases; however, the creases may not be specific because the development of a horizontal mental crease is not rare in individuals with advanced age. Taylor et al 9 reported tumefactive lipedema with PXE-like microscopic changes. The patient could have either a subclinical form of PXE, perhaps predisposing to lipedema, or secondary elastic tissue changes resulting from the massive edema.…”
Section: Discussionmentioning
confidence: 99%
“…An article published in 2004 by Taylor et al showed that accumulation of mast cells in lipedema tissue contributed to increased interstitial fluid, deterioration of adipocytes and potentially elastic fiber fragmentation due to the release of elastase [55], confirming that lipedema is a connective tissue disorder. Adding to that, direct cellcell interaction between hypertrophic adipocyte and macrophages as well as secreted paracrine factors such as vascular endothelial growth factor (VEGF), a marker of angiogenesis, previously reported in the blood of women with lipedema [56] might be associated with increase in the number of blood vessels, dilation of capillaries, hypoxia, inflammation and tissue fibrosis found in lipedema patients [15,18,57].…”
Section: Adipocytes Immune Cells and Blood Vesselsmentioning
confidence: 98%